2020
DOI: 10.1126/sciadv.abb0413
|View full text |Cite
|
Sign up to set email alerts
|

In situ observation of nanolite growth in volcanic melt: A driving force for explosive eruptions

Abstract: Although gas exsolution is a major driving force behind explosive volcanic eruptions, viscosity is critical in controlling the escape of bubbles and switching between explosive and effusive behavior. Temperature and composition control melt viscosity, but crystallization above a critical volume (>30 volume %) can lock up the magma, triggering an explosion. Here, we present an alternative to this well-established paradigm by showing how an unexpectedly small volume of nano-sized crystals can cause a dispropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 76 publications
(157 reference statements)
6
72
0
1
Order By: Relevance
“…Consequently, the study of magma viscosity remains a central objective in physical volcanology as its parametrization feeds numerical models of volcanic eruptions (Gonnermann & Manga, 2013; Papale, 1999), pyroclastic density current scenarios (Ongaro et al., 2008), and ash‐cloud transport (Mastin et al., 2009) that are used for operational forecasting of eruption evolution and planning of emergency response and evacuation (Marzocchi et al., 2012). The viscosity of magmas spans 1031013 Pa s and is controlled by temperature (T), melt composition (x), micro and nanocrystals (Φc), and bubble (Φb) volume fraction (Bagdassarov & Dingwell, 1992; Caricchi et al., 2007; Chevrel et al., 2015; Cordonnier et al., 2009; Costa et al., 2009; Davì et al., 2009; Dingwell et al., 1996, 2004; Di Genvova, Brooker, et al., 2020; Di Genova, Kolzenburg, et al., 2017; Di Genova, Romano, Alletti, et al., 2014; Di Genova, Zandona, & Deubener, 2020; Dobson et al., 1996; Giordano et al., 2009; Hess et al., 2001; Ishibashi & Sato, 2007; Kolzenburg et al., 2018; Lejeune et al., 1999; Liebske et al., 2003, 2005; Manga et al., 1998; Misiti et al., 2011; Mueller et al., 2010; Norton & Pinkerton, 1997; Pistone et al., 2012; Richet et al., 1996; Robert et al., 2013; Romano et al., 2003; Sehlke et al., 2014; Stabile et al., 2016; Stagno et al., 2018; Stein & Spera, 2002; Vetere et al., 2008, 2013; Vona et ...…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the study of magma viscosity remains a central objective in physical volcanology as its parametrization feeds numerical models of volcanic eruptions (Gonnermann & Manga, 2013; Papale, 1999), pyroclastic density current scenarios (Ongaro et al., 2008), and ash‐cloud transport (Mastin et al., 2009) that are used for operational forecasting of eruption evolution and planning of emergency response and evacuation (Marzocchi et al., 2012). The viscosity of magmas spans 1031013 Pa s and is controlled by temperature (T), melt composition (x), micro and nanocrystals (Φc), and bubble (Φb) volume fraction (Bagdassarov & Dingwell, 1992; Caricchi et al., 2007; Chevrel et al., 2015; Cordonnier et al., 2009; Costa et al., 2009; Davì et al., 2009; Dingwell et al., 1996, 2004; Di Genvova, Brooker, et al., 2020; Di Genova, Kolzenburg, et al., 2017; Di Genova, Romano, Alletti, et al., 2014; Di Genova, Zandona, & Deubener, 2020; Dobson et al., 1996; Giordano et al., 2009; Hess et al., 2001; Ishibashi & Sato, 2007; Kolzenburg et al., 2018; Lejeune et al., 1999; Liebske et al., 2003, 2005; Manga et al., 1998; Misiti et al., 2011; Mueller et al., 2010; Norton & Pinkerton, 1997; Pistone et al., 2012; Richet et al., 1996; Robert et al., 2013; Romano et al., 2003; Sehlke et al., 2014; Stabile et al., 2016; Stagno et al., 2018; Stein & Spera, 2002; Vetere et al., 2008, 2013; Vona et ...…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that pre-eruptive H 2 O melt contents from melt inclusions in the GT [H 2 O ≤ 4.2 wt%, Lanzo et al, 2013] are comparable with contents from much lower explosivity pantellerite eruptions (H 2 O max = 4.4 wt%, Gioncada and Landi [2010]) and with H 2 O melt inferred from phase equilibria experiments [Di Carlo et al, 2010, Romano et al, 2020. This evidence may suggest that other than the pre-eruptive H 2 O melt eruptive triggers must be considered; one might be related to an abrupt syneruptive viscosity increase due to nanolites growth [Càceres et al, 2020, Di Genova et al, 2020.…”
Section: Welding and Rheomorphismmentioning
confidence: 54%
“…A recent experimental study by Di Genova et al (2020) revealed that nanolite precipitation is a transient phenomenon that is preserved at a high cooling rate of 10-20°C/s, whereas slow cooling allowed microlites to form. Di Genova et al (2020) suggested that a small amount (~ 4 vol.%) of nanoparticles and a shear rate of 3.5 s -1 would increase the viscosity by a factor of 10 2 within 100 s of nanolite formation.…”
Section: Different Color Types Of the Drift Pumice Clastsmentioning
confidence: 99%
“…A recent experimental study by Di Genova et al (2020) revealed that nanolite precipitation is a transient phenomenon that is preserved at a high cooling rate of 10-20°C/s, whereas slow cooling allowed microlites to form. Di Genova et al (2020) suggested that a small amount (~ 4 vol.%) of nanoparticles and a shear rate of 3.5 s -1 would increase the viscosity by a factor of 10 2 within 100 s of nanolite formation. Given that the brown-colored glass of the present study contains nanolites and that this increased its viscosity, this can explain the less deformed texture of the black pumice as compared with the gray pumice (Fig.…”
Section: Different Color Types Of the Drift Pumice Clastsmentioning
confidence: 99%